Applied Contingency Table with Qualitative Focus Group on Occupational Health and Safety Management Perceptions of Operation and Leader in Medium Construction - Daoden, Kanchana; Kornpitak, Thuttha (International Journal of Psychosocial Rehabilitation, 2024)
Prevention and management health and risk of the workers which involved construction firms were realized that higher than other divisions and acknowledged in different contexts. However, it is a fewer phenomenon which the workers will attend to the organization in preventing and managing strategies of their health and risks instead of roughly regulate from the centralized policy. In this current study, we explored the interrelation of major factors, including how it affected the decision making of worker and organization attitudes when dealt with accident and hazard in the workplace. Moreover, we focus on the individual characteristics of the worker for accidental risk perception under the organization. Methods: An individual basic information questionnaire, risk behavior perception questionnaires, short interview and a focus group study performed with a sample of 150 participants; workers, head workers, officers, managers, and executives division aged between 18–69 years of medium enterprises. The participants divided into two main groups as 60 peoples of the leader (policy) group and 90 peoples of operation groups. Both groups randomized from 3 small provinces of northern Thailand. All of them will receive a specific questionnaire regard to their opinion and vision on accident hazards in the workplace (protection plan and responsibility). After that, the operation groups will divide into ten focus groups and six of leader groups The participants in each operation group will be encouraged to express their views about their hazard experiences and propose the ways to reduces accident in the workplace and summarize the group's comments to share the point of view to other groups. The analysis was conducted by thematic method and descriptive statistics, searching for significant factors and themes describing the participants’ experiences. Results: Five main themes of operation groups occurred for anticipating and dealing with accidents during work: (1) appropriate working conditions/environment, (2) prepare for occurring events, (3) having clear OSH policy, (4) assign proper work, and (5) representative manager response. In case of leader groups four general themes emerged during discussion: (1) preparing/readiness of the workers, (2) work skills, (3) working time, and (4) workplace conditions. Conclusion: The results show different concepts in dealing with dangerous situations or accidents that may occur during the work of both groups. (Workers and Leaders), where workers are recognized and aware of the risks that are nearby them like the work environment, then expand to other topics while the leader group will see the opposite. Most of the leaders misunderstood about roles and responsibilities for health and safety at work, including lack of sincerity, no commitment to action, and may not truly realize the consequences of not paying attention to preventing and reducing accidents during actual work of the company. The study shows the potential to develop better organizational strategies based on the worker's aspects, together with policymakers, to prevent the accidental risk from working.